Cherenkov diffraction radiation generated by 3D printed plastic samples; Charged & Neutral Particles Channeling Phenomena – Channeling 2024 - Kubankin A. S. Aleksandr Sergeevich; Bulavskaya A. A. Angelina Aleksandrovna; Baldin A. A. Anton Aleksandrovich; Klenin A. A.; Kidanova E. A. Ekaterina Alekseevna; Bushmina E. A. Elizaveta Alekseevna; Miloichikova I. A. Irina Alekseevna; Kishin I. A.; Nozdrin M. A.; Karataev P. V. Pavel Vladimirovich; Stuchebrov S. G. Sergey Gennadevich; Alekseev S. V.; et al. (2024, 2024)
In this study, a series of experimental samples were produced using the fused filament fabrication technique. The set comprised dielectric wafers printed from a variety of polymers, including polyethylene terephthalate glycol (PETG), polylactide (PLA), acrylonitrile butadiene styrene (ABS), high impact polystyrene (HIPS), styrene-acrylonitrile (SAN) and PLA with differing concentrations of impurities, including copper, bronze, carbon and wood fibre powder. A terahertz laser was applied to measure the refractive index and absorption plus reflection coefficient. Based on the data obtained, the most optimal materials were selected, from which test samples with a special geometry were manufactured for the ChDR generation.